PoincarÃ© Plot Method for Physiological Analysis of the Gadget Use Effect on Children Stress Level - Umar Zaky; Afwan Anggara; Muhammad Zakariyah; Ilham Fathullah (Department of Informatics, UIN Sunan Gunung Djati Bandung, 2022)
Stress in children can affect the way they think, act, and feel. The habit of using gadgets has several advantages and disadvantages, but there has been no in-depth study of the effect of using gadgets on stress levels in children. This study aims to determine the representation of the physiological condition of using gadgets on stress levels in children. A total of 18 electrocardiogram data were extracted with poincarÃ© plot features. This research has found that there is no difference in the level of stress in children between before and after using gadgets in terms of autonomic nervous activity (Sig. > 0.05). However, there is an increase in sympathetic activity that occurs in children even though they have finished using gadgets. Such conditions certainly need to get more attention, especially related to the duration of gadget use and accessible content.